Human rights in Southeast Asia: Comparing Malaysia and the Philippines - Taya, Shamsuddin L. (2013)
This article is a comparative study of human rights issues in Southeast Asia with particular focus between Malaysia and the Philippines.Its approach is primarily an eclectic, by concentrating on the strengths and weaknesses of the human rights regimes as practiced by both countries.This paper is divided into three parts.The first part looks at the six fundamentals of human rights that include: Respect for the integrity of the person; respect for civil liberties; and respect for political rights, more specifically, the rights of citizens in Malaysia and the Philippines to change their governments.The second part looks at the Malaysian and Filipino governments‟ attitudes regarding international and non-governmental investigation of alleged violations of human rights, such as discrimination based on religion, race/tribe, gender, disability, language or social status.The last part looks at worker‟s rights.The data for this analysis comes from primary and secondary sources, namely newspapers, the Internet, books, magazines and journals.The study found that the records of human rights in Malaysia is relatively good when compared to her ASEAN neighbour; the Philippines.For instance, Malaysia‟s experiences demonstrate that parliamentary democracy have been well-maintained in that elections have been held regularly ever since independence in 1957 compared to the disruption of the regular elections in the Philippines caused by the so-called “EDSA” Revolutions or People Power Revolutions.Indeed, Malaysia enjoys one of the fastest-growing economies and is one of the „Asian small tigers.‟ It may have occasional political and religious arrests of some opposition leaders, but physical force is not/and/or rarely exerted against opponents, in contrast to what Ferdinand E. Marcos and Gloria M. Arroyo did in the Philippines.Furthermore, there is nothing that resembles the violence that frequently erupts in the Philippines and the continuing human rights abuses committed by the Armed Forces of the Philippines (AFP) and its agents against its people.